Globalization vs. Glocalization: Learn Lessons from Two Global Crises, Such as the Russia–Ukraine Conflict and the COVID-19 Pandemic, for the Agro-Food and Agro-Industrial Sector - Tomas Gabriel Bas (Agriculture)
This article analyses the impacts of the Russia–Ukraine conflict and the COVID-19 pandemic on the supply chain and logistics related to the management of agro-food production based on a comprehensive review of the scientific literature. The challenges and lessons posed by market dependence in a scenario of globalization through monopolies and oligopolies in the production and export of agro-food are assessed, highlighting the vulnerability and uncertainty faced when an international conflict occurs. The review examines the format of globalization versus glocalization, analyzing their respective advantages and disadvantages in supply chains and management in the context of two major crises such as the COVID-19 pandemic and the armed conflict between Ukraine and Russia. Likewise, the resilience of agro-food and agro-industrial systems that were negatively affected by food insecurity and food price inflation in parts of Europe, Africa, and other regions of the planet is analyzed. By identifying opportunities arising from these challenges, the research offers insights into fostering a more robust agro-food supply chain that is more adaptable to global crises based on the geographic location and regional development of agribusinesses capable of responding to demand in the event of a global crisis such as a pandemic or armed conflict.